Knowledge as A Factor That Affects The Validity and Interest in Carrying out Islamic Law - Tasurun Amma; Muhammad Anwar Rifa'i (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Zakat is a form of worship that requires knowledge to support the validity of worship and also encourage the interest of a Muslim to carry out his obligations. This article seeks to explain how knowledge about zakat can support the validity and also encourage interest from the perspective of madhhab Shafi'i . This research was carried out with a quantitative approach with analytical methods based on Partial Modeling Least Square. The data collection technique uses a questionnaire that contains latent variables and observed variables which are indicators of the variables themselves, the research sample is 100 respondents with the population criteria of religious leaders, community leaders, and ordinary people who are based in schools of thought. Shafi'i. The results of the study explain that knowledge has a positive and significant effect on the validity of community zakat, which means that in order for a community's zakat to achieve its goal of being legal, sufficient knowledge of the terms, pillars, and other provisions of zakat is needed. Furthermore, knowledge also has a positive and significant effect on people's interest in carrying out zakat obligations, the higher a person's knowledge of zakat, the higher his interest in zakat.